«Ten Minutes with the Prime Minister» as a New Interlocutory Conversational Genre in the Ukrainian Political Discourse (Linguostylistic Studies, 2017)
The article reports on the research which is interdisciplinary in nature and highlights the problems of political and communicative linguistics in the domain of interlocutory conversational genres. The genre space of the Ukrainian political communication is considered with an emphasis on one of the modern Ukrainian political discourse genres revealed in the case study of the TV program «Ten Minutes with the Prime Minister». The author argues that this substyle of the political conversational genre combines elements of political appeal, political report and political program. The article revises the basic theories that shed light on the concept of speech genre, the issues of defining speech genres and the principles of their typology, describes the peculiar text-forming features of the conversational genre of the «Ten Minutes with the Prime Minister». The study findings indicate to the syncretic character of the analyzed speech genre since it combines the elements of factuality and information in it. The analysis of structural-semantic and linguopragmatic parameters of this conversational genre contributes to understanding of the specificity of the speech behavior of the politician as a linguistic personality. The implicit dialogic nature of the «Ten Minutes with the Prime Minister» genre is substantiated, placing importance on the markers of dialogue and the main language means of representing the setup on the addressee. The study has been performed on the material of the ex-Prime Minister of Ukraine A. Yatseniuk’s speech messages, represented in the TV programs «Ten Minutes with the Prime Minister» during 2015–2016.
Keywords: political discourse; speech genre; language behavior; factuality; information; dialogic